Exploring Upper Primary School Novice EFL Teachers Application of Pedagogical Content Knowledge during Speaking Lessons: The Case of East Shawa Zone, Ethiopia - Wakjira Gabisa Dhinsa; Melaku Wakuma Duguma (LET: Linguistics, Literature and English Teaching Journal)
There have been contentions on the significance between content and pedagogical knowledge among language scholars. The introduction of PCK (Pedagogical Content Knowledge) seems to merge the disparity. PCK is a special amalgam between content and pedagogy, which is unique to teachers and especially to experienced teachers. However, teacher training institutions place different emphasis on content and pedagogy. As a result, novice teachers encounter various challenges in their professional career in applying appropriate PCK in the classrooms. This study was aimed at exploring EFL novice teachers’ implementation of PCK in upper primary schools during speaking lessons. The results show that upper primary school EFL novice teachers had gaps in Subject Matter Knowledge (SMK) and PCK to teach EFL speaking skills though they believe that they are equally important to teach speaking skills which they consider as one of the most difficult areas for them to teach. Hence, teacher training colleges need to provide trainees with strong content and pedagogical backgrounds.